Controlled release tablet formulation containing natural Δ9-tetrahydrocannabinol. (2nd July 2016) - Punyamurthula, Nagendra S.; Hingorani, Tushar; Adelli, Goutham; Gul, Waseem; ElSohly, Mahmoud A.; Repka, Michael A.; Majumdar, Soumyajit
Abstract: Cannabinoids are increasingly being used in the treatment of chemotherapy-induced nausea and vomiting (CINV) because of their action on the cannabinoid receptors, CB1 and CB2. The currently marketed capsule formulations (sesame oil based and crystalline powder) are required to be administered frequently to maintain therapeutic levels, which leads to non-compliance. In the present study, oral controlled release tablet formulations of Δ 9 -tetrahydrocannabinol (THC) were prepared using the lipids Precirol® and Compritol®. Release profiles using THC-lipid matrices and/or with the lipids in the external phase (blend) were evaluated. The effect of directly compressible diluents lactose mixture (Ludipress®), dicalcium phosphate anhydrous (Emcompress®) and microcrystalline cellulose (Avicel® 102) on tablet characteristics and in vitro drug release was also investigated. Further, in vitro THC release in the presence of a lipase inhibitor, Pluronic® F68, was also studied. A 24 h zero-order THC release profile was obtained with a combination of Precirol® and Compritol® in the compression blend. Addition of Pluronic® F68 did not alter THC release in vitro . These optimized tablets were chemically and physically stable for 3 months, the last time point tested, at 25 °C/60% RH. The overall results demonstrate the feasibility of preparing oral THC tablets for once a day administration which can improve CINV management.